2017
DOI: 10.5194/gi-6-293-2017
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of morphometric features for adequate water resource management in arid environments

Abstract: Abstract. Hydrological characteristics such as topographic parameters, drainage attributes, and land use/land cover patterns are essential to evaluate the water resource management of a watershed area. In the current study, delineation of a watershed and calculation of morphometric characteristics were undertaken using the ASTER global digital elevation model (GDEM). The drainage density of the basin was estimated to be very high, which indicates that the watershed possesses highly permeable soils and low to m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 28 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Saudi Arabia is located in a geographical area lacking fresh water and has no natural resources such as springs, rivers, and lakes with scarcity or lack of rainfall in some areas. Natural resources in the Kingdom are limited to some wells, rainwater pools, and floods that have not been sufficient to meet the essential needs (Elhag et al, 2017b).…”
Section: Study Area Descriptionmentioning
confidence: 99%
“…Saudi Arabia is located in a geographical area lacking fresh water and has no natural resources such as springs, rivers, and lakes with scarcity or lack of rainfall in some areas. Natural resources in the Kingdom are limited to some wells, rainwater pools, and floods that have not been sufficient to meet the essential needs (Elhag et al, 2017b).…”
Section: Study Area Descriptionmentioning
confidence: 99%
“…Location of Wadi Yalamlam (Bahrawi et al, 2016). El-Kady et al, 1995;Shaltout and Mady, 1996;Shaltout et al, 1997). The flora of Saudi Arabia is reasonably well identified at the taxonomic level.…”
Section: Introductionmentioning
confidence: 96%
“…The height of these mountains reaches up to 2850 m. Some researchers have demonstrated that the topography and climate of the area are affecting the level of speciation (Abulfatih, 1992; . El-Kady et al, 1995;Shaltout and Mady, 1996;Shaltout et al, 1997). The flora of Saudi Arabia is reasonably well identified at the taxonomic level.…”
Section: Introductionmentioning
confidence: 97%